Modelling a Conversational AI Chatbot for Academic Websites - Bhaskar, T; Dive, YA; Gujarathi, AJ; Gangurde, S.A.; Rajput, ND (International Journal of Computer Sciences and Engineering, 2022)
This project aims in developing a conversational chatbot for college universities, which can converse in any desired language. The main purpose of the planned system is to develop a chatbot which can intelligently answer all the queries related to universities. For this purpose, machine learning algorithms are used. Primarily, NLP (Natural Language Processing) is used for the interaction between the chatbot and the user. To answer the users query, many different machine learning algorithms can be used. For this purpose, we move to cosine similarity. It, in a way, helps the chatbot to search for the answer to the user's query. Also, various libraries are used for different purposes like accepting the audio input, converting speech to text, translating to desired language, etc. The pandemic has affected a lot of fields around the world. One of them is the educational field. Many students in the urban as well as the rural parts of India were not able to visit the universities to get information about academics. This chatbot would eliminate these worries. All the information needed can be accessed online